(untitled) (International Journal of Scientific Trends, 2026)
The article aims to present an analysis of the influence that geometric and optical parameters exert on the energy efficiency of bifacial PV modules. The installation height, tilt angle, and surface albedo have been studied with experimental data and with a proposed mathematical model. The results confirm that increasing the installation height to a range between 0.7 m and 1.0 m and choosing an optimal tilt angle between 30° and 35° reduces power losses due to uneven illumination by over 25% and improves energy production. The spectral characteristics of the surface albedo have a profound effect on the value of the bifacial enhancement. The satisfied results of the calculated and experimental tests (R²>0.9) confirm the applicability and viability of the proposed model.